STUDYING THE AGROCHEMICAL EFFICIENCY OF GROWTH STIMULANTS BASED ON COBALT CARBOXYLATE IN COTTON GROWING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The growth regulatory activity of coordination compounds based on their biological activity has been studied. According to the results of laboratory and vegetative studies, it was found that Co(Hit)2•K•AHK - dinitrate urea nicotinamide cobalt coordination compound has biologically active properties that enhance the growth and development of plants.